Availability and variability in guidelines on diabetic retinopathy screening in Asian countries. Issue 10 (14th March 2017) - Wang, Louis Zizhao; Cheung, Carol Y; Tapp, Robyn J; Hamzah, Haslina; Tan, Gavin; Ting, Daniel; Lamoureux, Ecosse; Wong, Tien Yin
Abstract : Background: Diabetic retinopathy (DR) is a blinding yet treatable complication of diabetes. DR screening is highly cost-effective at reducing blindness. Amidst the rapidly growing diabetic population in Asia, the prevalence of DR in the region is relatively less well known. Aims: To review existing national DR screening guidelines of 50 countries in Asia, compare them against the International Council of Ophthalmology (ICO) guideline, and summarise the prevalence rates of DR and sight-threatening DR (STDR) in these countries. Methods: We systematically searched for published guidelines from the National Guideline Clearinghouse and other databases, and contacted local diabetic and ophthalmological associations of all 50 Asian countries. Results: Eleven Asian countries have published relevant guidelines, nine of which pertain to general diabetes care and two are DR-specific, covering less than half of Asia's population. The median DR prevalence among patients with diabetes is 30.5% (IQR: 23.2%–36.8%), similar to the USA and the UK. However, rates of STDR are consistently higher. All guidelines from the 11 Asian countries fulfil the ICO standard on when to start and repeat screening, except for screening interval for pregnant patients. However, only 2 of the 11 guidelines fulfil the ICO referral criteria and 6 partially fulfil. A third of the recommendations on screening process, equipment and personnel is either unavailable or incomplete. Conclusions: Countries in Asia need to establish more comprehensive and evidence-based DR screening guidelines to facilitate the execution of robust screening programmes that could help reduce DR-related blindness, improve patient outcomes and reduce healthcare costs.